Nitrogen Availability, Maturity and Stability of Bokashi-Type Fertilizers Elaborated with Different Feedstocks of Animal Origin - Quiroz-Espinoza, M; Flores-Kossack, C (Taylor and Francis Ltd., 2019)
Organic amendments, such as bokashi, are applied to the soil to increase the N. However, the available N provided by these fertilizers and the feedstocks with which they are produced have been poorly documented. In this work, the available N in bokashi was evaluated as well as their biological stability and chemical maturity. The treatments bokashi poultry (WVP); bokashi swine (WVS) and bokashi control (WVC) contained wheat straw and vegetable wastes; WVP and WVS also included poultry and swine manure, respectively. The temperature, mineral N, pH, EC, CO 2 production rate and germination index (IG) were measured. At the end of the trial, all of the treatments’ temperatures exceeded room temperature. The WVP presented a higher mineral N (1,054 mg kg −1 ) than the WVS (844 mg kg −1 ) and the WVC (907 mg kg −1 ). In all treatments, the NH 4 + and NO 3 − decreased. EC reached phytotoxicity levels in all treatments (EC > 3 dS m −1 ). None of the treatments showed biological stability or chemical maturity (IG of WVP, WVS and WVC: 10%, 29% and 19%, respectively). Therefore, it is concluded that applying these bokashi to soils could limit crop growth due to phytotoxic effects and immobilization of transient N. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.